Student Perceptions of a Trial of Electronic Text Matching Software: A Preliminary Investigation - Green, D.; Lindemann, I.; Marshall, K.; Wilkinson, G. (Journal of University Teaching and Learning Practice, 2005)
It is accepted that using electronic detection methods has benefits within an overall strategy to promote academic integrity in an institution. Little attention has been paid to obtaining student perceptions to evaluate the cost/benefit of using such methods. This study reports on the evaluation of a trial of Turnitin software. 728 students responded to a survey about their thoughts on plagiarism and being involved in the trial. This study found that students were generally unsure about the benefits and whether the university should use the software. In particular, two groups of students showed significant differences to the rest of the students sampled. While Non English Speaking Background (NESB) students reported higher levels of perceived usefulness of the software, they also reported higher levels of anxiety about the impact on them. Law students reported lower levels of perceived usefulness of the software and higher levels of concern and mistrust. The impact of such perceptions on the learning environment needs to be investigated. Special attention may be needed in introducing such software to different groups of students in order to limit possible deleterious effects and enhance potential benefits.